Intrinsically ionic conductive cellulose nanopapers applied as all solid dielectrics for low voltage organic transistors - Shilei Dai (Nature Portfolio, 2018)
Next-generation organic electronics require flexible organic field effect transistors that show low-voltage operation and are biodegradable. Here, Huang and co-workers demonstrate high-performance transistors that utilize solid-state ionic conductive cellulose nanopaper as the dielectric.